Modifying Indonesian traditional games as media to improve English vocabulary of kindergarten and elementary schools’ students - Niswatin Nurul Hidayati (AL-ASASIYYA: Journal Of Basic Education, 2020)
Based on several sources, the English language proficiency of the Indonesian people is still in the low category. Indonesia is still below the average value of English language proficiency in the Asian region (53.00) or rank 5 below other ASEAN countries such as Singapore with a score (66.82), the Philippines (60.04), and Malaysia (58.55) at a very high level of proficiency, and Vietnam (51.57) in the intermediate proficiency level. The process of learning English can be carried out with a variety of media. However, because the object of the learning process is children, the use of modified traditional Indonesian games can be an option. This is because the world of children is the world of play. Indonesia has a lot of traditional games that can be utilized for the learning process, but in this case the writer focuses on offers to modify Kotak Pos, ABC Lima Dasar, and Engklek to be used for the learning process of children, in this case to improve children's vocabulary. Vocabulary is the focus of the writer because mastering a lot of vocabulary can be a very good capital for children to learn other language skills, for example speaking, writing, reading, and also listening. The author hopes that this writer's proposal can be used as a method used by parents and teachers to teach English in a fun way.